The life-world of youth in children's homes - Mudaly, Balasundran Subramani (Rhodes University, Faculty of Humanities, Department of Psychology, 1985)
The study sought to obtain an insightful understanding of the life-world of youth who have not only experienced long-term separation from their biological parents and families but who have also simultaneously experienced prolonged institutional life in a children'e home. Using a descriptive praxis in the context of an existential phenomenological perspective, the study elicited from participants written descriptions of their personal experiences of the phenomenon of self-fulfilment. The data were structurally analysed, expressed in the form of extended descriptions and utilised as the basis for an exposition/appreciation of the life-world relationships of institutional youth. The target group of teenagers was drawn from a specific children's home. However, in order to enhance the findings of the study, data from a comparative group of youth from intact families in the community were also utilised. The study yielded some useful comparative insights which not only formed the basis for certain recommendations but also served as directions for future research. Hopefully, these recommendations and research proposals will be of some immediate interest and comfort to both reeearchers and practitioners in the field of residential child and youth care
Keywords: Children -- Institutional care -- Psychological aspects; Self in children; Emotions in children; Identity (Psychology) in children